Joint Evaluation of Employment Guarantee Scheme of Maharashtra Status Report-Taluka Level Notes - Planning Commission (Planning Commission, 1977)
Baglan laluka, with 1,616 Sq. Km. of area spread over 150 villages and one town, and with 1.97 lakh population, accounts for 10.3% of area and 8.3% of population of Nashik district. Out of the population of 1.97 lakhs, as per 1971 Census, 0.78 lakhs (37.1%) were workers. Out of these, workers, 0.30 lakhs were cultivators and 0.33 lakhs were agricultural labourers. Baglan is the only tahsil in Nashik district, where the number of cultivators is less than the number of agricultural labourers. Out of the total population of 1.97 lakhs, the scheduled castes population was only 0.07 lakhs, but the scheduled tribes population was much more, at 0.58 lakhs.
Status Report-Taluka Level Notes